The Impact of SGLT1 Inhibition on Frailty and Sarcopenia: A Mediation Mendelian Randomization Study - Bang‐Bang Huang; Yu‐Jie Zhang; Guang‐Feng Ruan; Xing Yu; Qin Liu; Mei‐Jin Zhang; Ming‐Zhong Yu; Ai Chen; Ye‐Bei Liang; Liang‐Di Xie; Li Luo (Journal of Cachexia, Sarcopenia and Muscle, 2024)
ABSTRACT Background Although pharmacological effects of SGLT2 inhibitors on the development of frailty and sarcopenia were known, the role of SGLT1 remained less clear. The present study investigated the possible effect of SGLT1 inhibition on these conditions and explored potential mediators. Methods A two‐sample Mendelian randomization (MR) analysis was performed to assess the effect of SGLT1 inhibition on frailty index (FI) and low grip strength in individuals aged 60 years and older using both the FNIH and EWGSOP criteria. Subsequently, a two‐step MR analysis was conducted to investigate the mediating role of insulin resistance phenotype and identify potential mediators of the effect of SGLT1 inhibition on the FI and low grip strength from 1558 plasma proteins and 1352 metabolites. Results Genetically predicted SGLT1 inhibition was associated with decreased FI (β: −0.290 [95% CI: −0.399, −0.181]) and reduced risk of low grip strength in individuals aged 60 years and older under both FNIH (β: −0.796 [95% CI: −1.216, −0.376]) and EWGSOP criteria (β: −0.287 [95% CI: −0.532, −0.041]). The two‐step MR analysis demonstrated the role of insulin resistance phenotype in mediating SGTL1 inhibition on alleviating frailty (mediation proportion = 19.56% [95% CI: 8.42%, 30.70%]). After screening, 24 proteins and 16 metabolites were identified as mediators of the impact of SGLT1 inhibition on FI. Additionally, 13 proteins and 16 metabolites were found to mediate the effect of SGLT1 inhibition on low grip strength according to FNIH criteria while 22 proteins and 6 metabolites were shown to mediate the impact of SGLT1 inhibition on low grip strength under EWGSOP criteria. Conclusions SGLT1 inhibition potentially mitigated frailty and sarcopenia through several biological mediators, shedding new light for therapeutic intervention.